Vessel Motions and Mooring Line Tensions in very Shallow Water - Cavefors, Johan; Oscarsson, Andreas (My University, 2016)
This thesis focus on the motions of a vessel operating on a very low keel clearance. To save time and money, it is efficient if one cable laying vessel can get a cable all the way to shore without the need to change vessel. This means that the vessel will operate on very shallow water close to shore with many shallow water effects affecting the movement. No international standard covers movement in very shallow water operations. Therefore, this investigation has been made on a cable laying vessels motions and its corresponding mooring line tensions. A model has been set up in ANSYS Aqwa which has been validated through several steps. The model has been run with various significant wave heights and wave periods as well as analysed with different wave angles. Different parameters, such as wind, current, wave spectra and water depths has been varied and presented in graphs. The results show a small influence from the wind and current on the mooring line tensions but very little on the motions. The wave angle influences the results significantly with peak motions around an angle perpendicular to the vessel and relatively small motions when hitting the vessel from the bow or stern. Due to some limitations and assumptions, the results can be considered slightly conservative. Despite this, they should be used with caution as no verification of the model has been made. During the summertime, operation lasting for several days should be possible since movements resulting in a grounding are very unlikely during this time. Operations in wintertime should also be possible but more caution is needed and shorter time windows are likely. To further investigate the problem, more different simulation cases needs to be run where the different parameters are varied more. A physical model should also be built in order to validate the results. Furthermore, ANSYS Aqwa has some limitations. To receive an even more accurate solution, the model might need to be set up in a more advanced program which allows further adjustment of the model, such as OPENFOAM or similar.
Keywords: Transport; Hållbar utveckling; Transportteknik och logistik; Transport; Sustainable Development; Transport Systems and Logistics